Clinical aspects for differential diagnosis of Kawasaki disease shock syndrome: a case control study - Woo Young Park; Sang Yun Lee; Gi Beom Kim; Mi Kyoung Song; Hye Won Kwon; Eun Jung Bae; Eun hwa Choi; June Dong Park (BMC, 2021)
Abstract Background Because of the absence of a specific diagnostic test and pathognomonic clinical features, physicians must rely on the presence of specific clinical criteria and laboratory data that support the diagnosis of KD. To help clinicians distinguish KD, KDSS, septic shock, and TSS earlier, we suggest differential diagnosis and treatment guideline. Methods Medical records of immunocompetent patients who were admitted to the pediatric department with a diagnosis of KDSS, septic shock or TSS (SS group) were retrospectively reviewed. In addition, KD patients were selected by seasonal matching to each case of KDSS patient by date of admission (± 2 weeks). Results There were 13 patients with KDSS, 35 patients with SS group, and 91 patients with KD. In comparison between KDSS and septic shock group, KDSS group had significantly higher rate of coronary aneurysm incidence, and higher left ventricle dysfunction rate. In comparison between KDSS and TSS, patients with KDSS had a significantly higher erythrocyte sedimentation rate (ESR) and significantly lower creatinine. Receiver operation characteristic curve revealed that the optimal ESR cut off value for determining the KDSS was 56.0 (sensitivity 75.0%, specificity of 100.0%) and the optimal creatinine cut off value for determining the TSS was 0.695 (sensitivity 76.9%, specificity 84.6%). Conclusions Clinical symptoms, laboratory finding, echocardiography, and culture studies can be used to differentiate KD, KDSS, septic shock and TSS.